Pressure to the P6 Acupoint and Post - Appendectomy Pain, Nausea, and Vomiting : A Randomized Clinical Trial - Mohsen Adib - Hajbaghery; Mahmood Etri; Masoumeh Hosseainian; Masoumeh - Sadat Mousavi (Journal of Caring Sciences, 2013)
Introduction: The use of acupressure is growing. Several studies have applied pressure to the P6 to reduce postoperative nausea, vomiting, and pain but have reported conflicting results. This study aimed to investigate the effects of pressure to the P6 point on pain, nausea and vomiting after appendectomy. Methods: A single-blind, randomized controlled clinical trial was conducted on 88 patients after appendectomy. The subjects were randomly assigned to two groups. After the patients in the intervention group had regained their consciousness, pressure was applied to the P6 acupoint using special Acubands. In the control group, the Acubands were fastened loosely on the patients' wrists. The bracelets were kept for seven hours and pain, nausea, and vomiting were measured hourly. Student’s t-test and chi-square test were used to analyze data. All analyses were performed in SPSS11.5. Results: The two groups were not significantly different in terms of age, body mass index, duration of anesthesia, and length of incision. The mean pain intensity in the two groups was not significantly different at different times. Overall, 45.4% of the P6 group and 47.7% of the control group experienced postoperative nausea. The two groups were not significantly different in the mean intensity of nausea at different postoperative hours. In total, 12 patients in the P6 group and 18 in the control group had vomiting Conclusion: Pressure to the P6 did not significantly reduce pain and nausea after appendectomy. However, the incidence of vomiting was less in the P6 group. This method can be used to reduce vomiting after appendectomy. Similar studies are suggested to apply pressure with the onset of pain or nausea and vomiting.